Peut-on produire des inégalités justes dans un monde de promotion de l'égalité ? - François Dubet (Éducation et Socialisation)
Within the framework of Equality which appears at the front of all France town halls, the only way to decide between people is to organize a meritocratic competition. However, the creation of the French school system was not concerned with this imperative since until the 1960s, the French 11-plus exam had perpetuated a distribution between the very large minority of those who went to High School then held the most important positions in society and the vast majority who only attended primary school found employment easily. It wasn't all about academic excellence yet. With the successive waves of mass education and the rise in the level of education, a paradoxical gap has developed between the winners of the system and the losers who have been humiliated. The efforts of the system should be focused on them because they are victims of a model of extreme cruelty.